SPE Improved Oil Recovery Conference 2018
DOI: 10.2118/190209-ms
|View full text |Cite
|
Sign up to set email alerts
|

Identification, Problem Characterization, Solution Design and Execution for a Waterflood Conformance Problem in the Ekofisk Field - Norway

Abstract: This paper discusses a field case review of the processes used to identify, characterize, design and execute a solution for a waterflood conformance problem in the Ekofisk Field that developed in late 2012. The Ekofisk Field is a highly-fractured Maastrichtian chalk reservoir located in the Norwegian sector of the North Sea. Large scale water injection in the field began in 1987 and overall the field has responded well to waterflood operations. However, fault reactivation coupled with extensive natural fractur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Unfortunately, for various reasons (most commonly, financial or manpower-related), adequate characterization of the water production problem often does not occur. To help this situation, many people have offered strategies to attack water production problems (Aamodt et al 2018;Chou et al 1994;Elphick and Seright 1997;Kabir 2001;Love et al 1998;Mennella et al 1999;Pappas et al 1996;Seright et al 2003;Smith et al 2006;Soliman et al 2000;Sydansk and Romero-Zeron 2011) and suggested various categorizations of problems, in an attempt to simplify the analysis. The strategy that we advocate involves looking for and solving the easiest water production problems first.…”
Section: A Strategy To Attack Excess Water Production Problemsmentioning
confidence: 99%
“…Unfortunately, for various reasons (most commonly, financial or manpower-related), adequate characterization of the water production problem often does not occur. To help this situation, many people have offered strategies to attack water production problems (Aamodt et al 2018;Chou et al 1994;Elphick and Seright 1997;Kabir 2001;Love et al 1998;Mennella et al 1999;Pappas et al 1996;Seright et al 2003;Smith et al 2006;Soliman et al 2000;Sydansk and Romero-Zeron 2011) and suggested various categorizations of problems, in an attempt to simplify the analysis. The strategy that we advocate involves looking for and solving the easiest water production problems first.…”
Section: A Strategy To Attack Excess Water Production Problemsmentioning
confidence: 99%
“…Permanent well and reservoir surveillance with PDG and time-lapse PTA is today employed in the oil and gas industry with focus on well performance and behavior with their changes during reservoir life-time, including fluid contact movements and recovery processes (Gringarten et al 2003), (Yaich et al 2012), (Ugoala et al 2013), (Rushatmanto et al 2017), (Suleen et al 2017), (Cassie et al 2018); well stimulations (e.g., acid and fracture jobs) and monitoring of well performance over time (Shchipanov et al 2014), (Shchipanov et al 2017a(Shchipanov et al , 2017b; and any kind of improved/ enhanced oil recovery pilots such as water shut-off (Aamodt et al 2018) and silicate injection (Skrettingland et al 2012), (Skrettingland et al 2014). Figure 1 illustrates typical timelapse pressure transient responses for sequential well shutins from (Shchipanov et al 2017a).…”
Section: Introductionmentioning
confidence: 99%
“…Further study (Shchipanov et al 2017b) has extended the scope of time-lapse PTA to deal with multiple rate pressure transients and step-rate test analysis to monitor performance of wells with induced fractures. Aamodt et al (2018) discussed water shut-off jobs with massive cement placement into an injection well to improve water conformance control, where permanent pressure surveillance and PTA, including combined flowing/shut-in analysis, were used to identify well communication and to monitor the job efficiency. Recent field study by Walker et al (2021) employed time-lapse PTA to monitor initial phase of production in a giant oil field, where well interference and boundary conditions of the reservoir were disclosed from analysis of time-lapse flowing and shut-in periods.…”
Section: Introductionmentioning
confidence: 99%